Two Interviews, Images of the Mobility Paths - Imbronito, Maria Isabel; Barletta Jr, Biagio Antonio (Revista Nacional de Gerenciamento de Cidades, 2021)
This document compares two videos that date from the same year (1969) and provide a basis for discussion about two different paradigms of urban thinking present in the 1960’s: an interview with Jane Jacobs on the show "The way it is", on Canadian broadcaster CBC, in which she disputes the plans to build Spadina Expressway in Toronto, and a presentation by the then Mayor of São Paulo, Paulo Salim Maluf, on the plans to build Elevado Presidente Costa e Silva (currently named Elevado João Goulart, nicknamed Minhocão [the Big Worm]), an elevated expressway in São Paulo. By confronting the videos, the antagonism of the discourses regarding the role of road infrastructure, the value given to the urban environment, and the idea of quality of urban life becomes clear. The materials are also an illustration of two different outcomes: the halting of the Spadina Expressway works in Toronto and the completion of the Minhocão works in São Paulo.